Weed suppressive traits of winter cereals: Allelopathy and competition. (February 2018) - Reiss, Antje; Fomsgaard, Inge S.; Mathiassen, Solvejg K.; Kudsk, Per
Abstract: Weed suppressive potential of 33 winter wheat, 24 winter rye and 11 winter triticale cultivars recently introduced to the Scandinavian market was investigated. Competitive traits recorded were early vigor, leaf area index and crop height. Allelopathic potential was assessed by analyzing plant root and shoot material by LC-MS/MS for their content of 12 phytotoxic metabolites of the chemical group of benzoxazinoids (BX). Total BX content was highest in rye, followed by triticale and wheat. Benzoxazinoid composition varied between species with non-methoxy substituted BX dominating in rye and methoxy substituted BX dominating in wheat and triticale. Principal component analysis exhibited a clear relationship of allelopathic and competitive traits, together explaining 62% of the variance in the data set. This result underlines the need for further investigations of the relative contribution of allelopathy and competition to weed suppression in future studies. Graphical abstract: Highlights: LC-MS/MS analysis of 12 benzoxazinoids (BX) in roots and shoots of winter cereals. Rye shows a higher allelopathic potential, compared to wheat and triticale. A PCA visualizes a strong relationship between competitive and allelopathic traits. Both, allelopathic and competitive traits determine weed suppressiveness.